EKINShI JÁHÁN URÍSÍNAN KEYINGI DÁWIRLERDE QARAQALPAQSTANDA KITAPXANALAR JAǴDAYÍ - Reymbaev, R.S. (SCIENCE and SOCIETY, 2025)
The article is devoted to the history of the formation and development of library science in Karakalpakstan in the post-war years. It also discusses the activities of city, district, rural, and republican libraries, the number of libraries, book collections, issues in library work, and the establishment of the Ministry of Culture.